Modulation of Caspase-3 Expression and Spermatogenic Cells by Urtica dioica Extract in Obesity-Induced Male Rats - Kabir Ardiansyah Tangkari; Jurnalis Gempaning Tyas; Harni Sutiani; Zaenudin; Dicky Mochammad Rizal; Jajar Setyawan (Published by Universitas Gadjah Mada, 2026)
Obesity is associated with impaired steroidogenesis and spermatogenesis through mechanisms involving hypogonadism, inflammation, and oxidative stress. Pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α) contribute to apoptotic signaling pathways, including caspase-3 activation, leading to germ cellloss. Urtica dioica contains bioactive compounds with reported antioxidant and anti-apoptotic properties. This study aimed to evaluate the effects of U. dioica extract on TNF-α and caspase-3 mRNA expression as well as spermatogenic cell counts of the testes of obese male Sprague Dawley rats. This experimental study employed a post-test-only control group design using 25 rats divided into five groups: healthy control (C1), obese control induced by a high-fat and fructose diet (C2), and three intervention groups receiving U. dioica extract at doses of 125 mg/kg (D1), 250 mg/kg (D2), and 500 mg/kg (D3) for four weeks. The results showed no significant differences in TNF-α mRNA expression were observed between the intervention groups and the obese control. In contrast, caspase-3 mRNA expression was significantly reduced in all U. dioica–treated groups comparedwith the obese control. No significant differences were observed in the number of primary or secondary spermatocytes among groups. However, spermatid counts were significantly higher in D2 and D3 groups compared with the obese control. In conclusion, U. dioica extract demonstrated potential anti-apoptoticeffects and was associated with improved post-meiotic spermatogenic outcomes in obese rats.